The terrible : a storyteller's memoir - Daley-Ward, Yrsa (Penguin Books, 2018)
"From the celebrated poet behind bone, a lyrical memoir--part prose, part verse--about coming-of-age, uncovering the cruelty and beauty of the wider world, and redemption through self-discovery and the bonds of family "You may not run away from the thing that you are because it comes and comes and comes as sure as you breathe." This is the story of Yrsa Daley-Ward, and all the things that happened--"even the terrible things. And God, there were terrible things." It's about her childhood in the northwest of England with her beautiful, careworn mother Marcia; the man formerly known as Dad (half fun, half frightening); and her little brother Roo, who sees things written in the stars. It's also about the surreal magic of adolescence, about growing up and discovering the power and fear of sexuality, about pitch-gray days of pills and powder and connection. It's about damage and pain, but also joy. Told with raw intensity and shocking honesty, The Terrible is a memoir of going under, losing yourself, and finding your voice"--